Robust Algorithm For Mining Association Rules - Vedad, Alireza; Podgornyy, Gordor (International Journal of Computer (IJC), 2012)
Genetic algorithm is an important algorithm of association rule mining. However, there is some issues that genetic algorithm easy to lead prematuring convergence and into the plight of local optimum. For resolving this issues, the paper improves the genetic algorithm that applies to the mining association rules.